Small_signal analysis of multiple virtual synchronous machines to enhance frequency stability of grid_connected high renewables - Thongchart Kerdphol; Fathin Saifur Rahman; Masayuki Watanabe; Yasunori Mitani; Komsan Hongesombut; Veena Phunpeng; Issarachai Ngamroo; Dirk Turschner (My University, 2021)
Abstract The virtual synchronous machine technology is considered as an important technique to effectively control the shortcomings of renewable energy‐based power electronics interfaces, providing backup inertia and regulating grid stability. Conventionally, the virtual synchronous machine with a large capacity is responsible for controlling the entire grid stability against renewable penetration. It is usually operated as a centralised control system. But what if virtual synchronous machines with small capacities are independently operated by their additional droop control schemes, and will they present better performance than the single virtual synchronous machine? This study proposes the multiple virtual synchronous machine system with different active power‐frequency ( P‐f ) droop characteristics to improve inertia support regarding frequency stability improvement. The comprehensive small‐signal modelling of the multiple virtual synchronous machine unit is designed to include the additional P‐f droop characteristics. Then, the dynamic characteristics (steady‐state and transient responses) and static stability of the multiple virtual synchronous machines are compared with the single virtual synchronous machine at the same rated capacity in both eigenvalue/sensitivity‐domain and time‐domain analysis. The obtained results reveal that the system with the presence of several virtual synchronous machines is more stable than the system with single virtual synchronous machine, maintaining stable and secure system operation during the contingency.
Keywords: SIGNAL (programming language); Microgrid Control and Optimization